Alone in Paradise: Exploring the Intersections of Gender, Ethnicity, Single Motherhood, Social Class, and Immigration - Lam, Gia; Collins, Sandra; Wong, Gina (Canadian Journal of Counselling and Psychotherapy, 2022)
There is a paucity of research that is centred on cross-cultural transitioning for single mothers who immigrate to Canada. Focusing on the intersections of gender, ethnicity, social class, single motherhood, and immigration increases the understanding of challenges affecting single, immigrant mothers. As part of a qualitative description study, we examined the complex experiences of immigrant women who had navigated cross-cultural transitions and single motherhood through the lens of their intersecting cultural identities and social locations. Purposeful sampling was used to recruit single, immigrant mothers from multiple counselling agencies in a western Canadian city. Content analysis of six semi-structured interviews elucidated the women’s experience experiences of gender and mothering discourses within various social contexts, the impact of intersectionality on their acculturation processes in Canada, their relationships with their children, and the challenges of economic and psychosocial acculturation. One overarching theme that was related to the contrasts between the women’s former world and new world formed a lens through which they made meaning of their lived experiences. Implications for counselling and social services are provided.